Exploring The Role of Self-Compassion and Psychological Capital on the Performance of Gunungkidul Batik MSMEs in the Digital Era - Ayu Wulan; Agung Novianto Margarena; Irsal Fauzi (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This investigation assesses the consequence of self-compassion on the performance of Batik micro, small, and medium enterprises (MSMEs) in Gunungkidul Regency, with psychological capital serving as an intermediary variable. The findings are intended to facilitate the development of MSME mentoring interventions that integrate both technical and psychological components, particularly to support MSMEs owners in addressing the challenges associated with digitalization. We conducted quantitative research involving 70 batik MSMEs in Gunung Kidul. By using a total sampling technique and online questionnaires, we were able to capture a comprehensive data set. These responses, measured on a Likert scale, were then analyzed through path analysis using SPSS 25 to ensure statistical precision. The study reveals a deep connection between a person's outlook and their career path output. Specifically, self-compassion was found to significantly boost psychological capital (0.619, p=0.000). In turn, this psychological strength translates into better work performance (0.326, p=0.008). Interestingly, while self-compassion directly improves performance (0.381, p=0.002), psychological capital is key and acts as a vital bridge, mediating the relationship between the two with a value of 0.202. By positioning psychological capital as a mediator, this research offers a fresh perspective on MSMEs success, a niche that remains largely unexplored. The takeaway is clear: sustainable performance isn't just built on hard skills. We recommend that policymakers and mentors prioritize the "inner game" of entrepreneurs, fostering psychological strengths and self-compassion as fundamental pillars for business excellence.